The Correlation of Macronutrient Intake, Natrium, and Nutritional Status With The Blood Pressure Of Elderly Women In The Village Of Mojowarno Jombang - Indriana, Hesti; Veni Indrawati, (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Hypertension or high blood pressure is a health issue and the leading cause of death in society every year. The increase in the prevalence of hypertension among the elderly showed the importance of understanding the relationship between macronutrient intake, sodium, and nutritional status with blood pressure so that it could be applied in clinical practice. This study is conducted to understand the relationship between macronutrient intake, sodium, and nutritional status with blood pressure in elderly women in Mojowarno Village, Jombang. This study was a quantitative research with a cross-sectional design with a sample size of 60 individuals. The respondents were elderly women aged 56-65 years and the research instruments were the 3 × 24 hour Food Recall form and the Mid Upper Arm Circumference (MUAC) tape measure. Data analysis used in this study was Pearson product Moment correlation test. The results of this study showed that macronutrient intake namely energy intake was related to blood pressure (p-value= 0.000), carbohydrate intake was related to blood pressure (systolic p-value= 0.000 and diastolic p-value= 0.001), fat intake was related to blood pressure (p-value= 0.000), and protein intake was related to blood pressure (systolic p-value= 0.001 and diastolic p-value= 0.002). Sodium intake was related to blood pressure (p-value= 0.000). Nutritional status was not related to blood pressure (systolic p-value=0.558 and diastolic p-value=0.064). Based on the results of this study, it could be concluded that macronutrient intake and sodium had a significant relationship with blood pressure in elderly women in Mojowarno Village, Jombang.